Konsep Pendidikan Akhlaq dalam Perspektif Islam - Anshory, Muhammad Isa; Azis, Muhamad Abdul; Chabib, Mudzakir; Sutrisno, Agus (Lembaga Yasin AlSys, 2025)
This study examines the concept of moral education in Islam using a literature review method. Data were collected from various authoritative written sources to analyze how moral education plays a role in shaping students' character. The findings indicate that high-quality education leads to good morals, which in turn shape individuals with integrity. Ideal education in Islam must be based on the Qur'an and Hadith as the primary sources of moral values. Islamic ethics possess distinct characteristics that differentiate them from other ethical systems, namely: (a) Rabbaniyah, sourced from Allah SWT and embodying divine values, (b) Insaniyah, ligned with human nature and needs, (c) Syumuliyah, universal and encompassing all aspects of life, and (d) Wasathiyah*, emphasizing balance in every aspect of life. Furthermore, this study emphasizes that moral education should begin at an early age, as childhood is the most effective period for instilling good habits.